Evaluasi dan Perbaikan Proses Pengiriman dan Pengantaran Pos untuk Mengurangi Tingkat Keluhan Pelanggan PT Pos Indonesia (Persero) Kcu Surabaya 60000 - Septi Teguh Satria; Indro Kirono (Dinasti Research, 2023)
Evaluation and Improvement of the Postal Delivery Process to Reduce the Level of Customer Complaints PT Pos Indonesia (Persero) Kcu Surabaya 60000. This study aims to evaluate and improve the POS delivery and delivery process to reduce the level of customer complaints. A high level of customer complaints can be an indicator of problems in the POS delivery process that can interfere with customer satisfaction and company reputation. Once the problems are identified, improvement measures are proposed and implemented. These improvement measures involve increased coordination between relevant departments, improved training and supervision of employees involved in the POS shipping and delivery process, as well as more effective and efficient use of technology and optimized supply chain management. The results of this study show that by implementing the proposed improvement measures, the level of customer complaints can be significantly reduced. Customers experience increased satisfaction with the POS shipping and delivery process, which in turn can have a positive impact on the company's reputation. This research makes an important contribution in improving the POS shipping and delivery process to reduce the level of customer complaints. The practical implication of this research is that companies can implement the proposed improvement measures to enhance their service quality and strengthen customer relationships. In addition, this study also provides direction for further research in the field of operations management and service delivery.